Experimental and theoretical study of photoluminescence and magnetic properties of metal–organic polymers based on squarate and tetrazolate moieties containing linkers. (23rd October 2015) - Seco, Jose M.; Calahorro, Antonio J.; Sebastian, Eider San; Salinas-Castillo, Alfonso; Colacio, Enrique; Rodríguez-Diéguez, Antonio
Abstract : Cd 2+, Zn 2+ or Co 2+ based luminescence and magnetic properties of isostructural metal organic chains. Abstract : We report on the synthetic, luminescence and magnetic properties of three new isostructural Zn-, Cd- and Co-based 1D coordination polymers with the novel 3-(1 H -tetrazol-5-ylamino)-4-hydroxycyclobut-3-ene-1, 2-dione spacer, consisting of a squarate and a tetrazolate moiety linked by a NH group. These compounds exhibit an intense blue-green photoluminescence emission at room temperature in the solid state (Cd- and Zn-based structures) and antiferromagnetic exchange interactions (Co-based materials).